Location, location, location: alterations in the functional topography of face- but not object- or place-related cortex in adolescents with autism - Scherf, K. Suzanne; Luna, Beatriz; Minshew, Nancy; Behrmann, Marlene (Frontiers in Human Neuroscience, 2010)
In autism, impairments in face processing are a relatively recent discovery, but have quickly become a widely accepted aspect of the behavioral profile. Only a handful of studies have investigated potential atypicalities in autism in the development of the neural substrates mediating face processing. High-functioning individuals with autism (HFA) and matched typically developing (TD) controls watched dynamic movie vignettes of faces, common objects, buildings, and scenes of navigation while undergoing an fMRI scan. With these data, we mapped the functional topography of category-selective activation for faces bilaterally in the fusiform gyrus, occipital face area, and posterior superior temporal sulcus. Additionally, we mapped category selective activation for objects in the lateral occipital area and for places in the parahippocampal place area in the two groups. Our findings do not indicate a generalized disruption in the development of the entire ventral visual pathway in autism. Instead, our results suggest that the functional topography of face-related cortex is selectively disrupted in autism and that this alteration is present in early adolescence. Furthermore, for those HFA adolescents who do exhibit face-selective activation, this activation tends to be located in traditionally object-related regions, which supports the hypothesis that perceptual processing of faces in autism may be more akin to the perceptual processing of common objects in TD individuals.